Soil Carbon Pools in Dryland Agroecosystems as Affected by Several Years of Drought. Issue 4 (1st July 2018) - Sherrod, L. A.; McMaster, G. S.; Delgado, J. A.; Schipanski, M. E.; Fonte, S .J.; Montenieri, R. L.; Larson, K.
Abstract : No‐till and increased cropping intensity (CI) can increase yield and soil organic C (SOC) in the US Great Plains compared with traditional wheat ( Triticum aestivum L.)–fallow management. However, gains in SOC and other C pools may not be permanent. Increasing frequency of drought may reduce C inputs and potentially reverse gains accrued during wetter periods. This study examined the effect of drought on the persistence of SOC with two objectives: (i) to determine soil C pools (0–20 cm) after 24 yr in no‐till as influenced by potential evapotranspiration (PET), landscape position (slope), and CI; and (ii) to compare the size of the C pools after the first 12 yr (wet) versus the subsequent 12 yr, notable for frequent droughts. Rotations were wheat–corn ( Zea mays L.)–fallow (WCF), continuous cropping (CC), and a grass Conservation Reserve Program mixture planted across slopes at three sites in Colorado with similar precipitation but increasing PET. After 24 yr, water‐soluble organic C increased with CI from WCF to CC to grass with 250, 340, and 440 kg C ha −1, respectively. Soil microbial biomass C also increased with CI–1500, 1660, and 2135 kg C ha −1 for WCF, CC, and grass, respectively. The particulate organic matter C pool had a three‐way interaction with PET, slope, and CI. Overall, between Years 12 and 24, SOC increased in grass by 16.9%, with a rate of 425 kg C ha −1 yr −1 sequestration compared with 10.5 and 1.4% for the WCF and CC systems, respectively. Core Ideas: Active C pools increased with cropping intensity at the end of both wet and dry years. Small changes in a large SOC pool are best predicted by measurement of POM‐C. Cropping system did not significantly influence the P‐MAOC pool after 24 yr. SOC levels showed resilience by maintaining or increasing during dry years.